Biomaterial scaffolds regulate macrophage activity to accelerate bone regeneration - Liu, Zongtai; Zhu, Jiabo; Li, Zhuohan; Liu, Hanyan; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2023)
Bones are important for maintaining motor function and providing support for internal organs. Bone diseases can impose a heavy burden on individuals and society. Although bone has a certain ability to repair itself, it is often difficult to repair itself alone when faced with critical-sized defects, such as severe trauma, surgery, or tumors. There is still a heavy reliance on metal implants and autologous or allogeneic bone grafts for bone defects that are difficult to self-heal. However, these grafts still have problems that are difficult to circumvent, such as metal implants that may require secondary surgical removal, lack of bone graft donors, and immune rejection. The rapid advance in tissue engineering and a better comprehension of the physiological mechanisms of bone regeneration have led to a new focus on promoting endogenous bone self-regeneration through the use of biomaterials as the medium. Although bone regeneration involves a variety of cells and signaling factors, and these complex signaling pathways and mechanisms of interaction have not been fully understood, macrophages undoubtedly play an essential role in bone regeneration. This review summarizes the design strategies that need to be considered for biomaterials to regulate macrophage function in bone regeneration. Subsequently, this review provides an overview of therapeutic strategies for biomaterials to intervene in all stages of bone regeneration by regulating macrophages.